USE OF FRP COMPOSITE MATERIAL FOR STRENGTHENING REINFORCED CONCRETE - Sultan Erdemli Gunaslan; Halim Karasin (European Scientific Journal, ESJ, 2014)
Fiber-Reinforced Polymers (FRP) can be classified as a type of composite material that is increasingly used in the construction industry in recent years. Due to their light weight, high tensile strength, corrosion resistance and easy to implementation makes these material preferred solution for strengthening method of reinforced concrete structural elements. In this study, literature’s experimental results are compared with American Concrete Institute (ACI440) and Turkish Seismic Design Code 2007 (TDY2007) in addition to mechanical properties of FRP material. The results of regulations have been evaluated and compared with experimental results. Consequently it has been noted that the FRP materials enhance both strengthening and ductility of reinforced concrete column sections.